METHODOLOGICAL FOUNDATIONS OF LEARNER CENTERED TEACHING TECHNOLOGIES IN PHYSICAL EDUCATION AND SPORTS TRAINING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the methodological foundations of learner-centered teaching technologies in physical education and sports training. The importance of organizing the educational process based on the individual characteristics of each student is substantiated. The practical effectiveness of this approach is demonstrated through international experience—advanced practices in the educational systems of the USA, Germany, and Japan. The paper outlines the ways to implement these methods in the local educational system and reveals their impact on students' socio-psychological development and the formation of sports culture through a learner-centered approach.